2014
DOI: 10.1128/jcm.02730-13
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Human Malawi Polyomavirus

Abstract: The seroprevalence of the recently discovered human Malawi polyomavirus (MWPyV) was determined by virus-like particlebased enzyme-linked immunosorbent assay (ELISA) in age-stratified Italian subjects. The findings indicated that MWPyV infection occurs early in life, and seroprevalence was shown to reach 42% in adulthood.T welve human polyomaviruses have been described to date, including JC and BK polyomaviruses (JCPyV and BKPyV), Karolinska Institute polyomavirus (KIPyV), Washington University polyomavirus (WU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 16 publications
5
35
4
Order By: Relevance
“…Seroprevalence to MWPyV (84.4%) was the second highest from all of HPyVs tested. Two recent studies reported MWPyV 42–75% in adulthood [Nicol et al, ; Berrios et al, ], which is slightly lower number compared to our findings. Seroprevalence to KIPyV (58%) agrees with numbers (55–70%) reported by others [Nguyen et al, ; Neske et al, ; Nicol et al, , ].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Seroprevalence to MWPyV (84.4%) was the second highest from all of HPyVs tested. Two recent studies reported MWPyV 42–75% in adulthood [Nicol et al, ; Berrios et al, ], which is slightly lower number compared to our findings. Seroprevalence to KIPyV (58%) agrees with numbers (55–70%) reported by others [Nguyen et al, ; Neske et al, ; Nicol et al, , ].…”
Section: Discussioncontrasting
confidence: 95%
“…So far, this phenomenon is not being observed frequently. Other studies did not find cross‐reactivity between MCPyV, TSPyV, HPyV9, and MWPyV VLPs or VP1s produced in bacteria [van der Meijden et al, ; Nicol et al, , ]. We found some degree of cross‐reactivity using HPyV6 and HPyV7 VLPs (r = 0.48), very similar to correlation (r = 0.43) between seropositive samples found in other study [Nicol et al, ].…”
Section: Discussionsupporting
confidence: 88%
“…1B). Similar findings for MWPyV were recently reported using a virus-like particle-based ELISA, with seroprevalence reaching 42% in an adult population (26). The moderately high levels of seroprevalence in children from age 3 to age 21 suggest that primary infection with MWPyV occurs in childhood, and the increasing frequency of elevated antibody titers that occurs with age is consistent with persistent lifelong infections.…”
supporting
confidence: 87%
“…Most mammalian polyomaviruses cause subclinical infections with lifelong persistence in their natural hosts. According to serological studies, asymptomatic infection occurs with 12 of the 13 known polyomaviruses detected in humans (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Polyomavirus-related diseases, which include nephritis (BK virus [BKV]) (15), encephalitis (JC virus [JCV]) (16), Merkel cell carcinoma (Merkel cell polyomavirus [MCV]) (17), skin dysplasia (trichodysplasia spinulosa-associated polyomavirus [TSV] and human polyomavirus 7 [HPyV7]) (18,19), and pneumonitis (Washington University [WU] virus [WUV]) (20,21), can occur among immune-suppressed individuals, including posttransplanta-tion and AIDS patients.…”
mentioning
confidence: 99%